Beachrock Formation Mechanism Using Multiproxy Experimental Data from Natural and Artificial Beachrocks: Insights for a Potential Soft Engineering Method - Giannis Saitis; Anna Karkani; Eleni Koutsopoulou; Konstantinos Tsanakas; Satoru Kawasaki; Niki Evelpidou (Journal of Marine Science and Engineering, 2022)
Beachrocks are a window to the past environmental, geological, sedimentological and morphological conditions that were dominant in the coastal zone during their formation. Furthermore, beachrocks have the ability to reduce coastal erosion impact on sandy beaches. This study focuses on the beachrock formation mechanism through the comparison of cement characteristics, mineral chemistry and sedimentology of beachrock occurrences from two different geological and geographical localities: Diolkos, Corinth, Greece and Sumuide, Okinawa, Japan. In addition, in order to investigate a potential soft engineering method to protect coasts from erosion, artificial beachrock samples were created in vitro using sand samples and ureolytic bacteria from both areas under accelerating conditions. For Okinawa artificial beachrock experiments, the bacteria Pararhodobacter sp. was used, and for Diolkos, it was the bacteria Micrococcus yunnainensis sp. For the natural beachrocks, a multi-analytical approach was accomplished with the use of microscopic investigation, a scanning electron microscope, energy-dispersive X-ray spectroscopy, X-ray diffraction and X-ray fluorescence. Correlations were made between natural and artificial beachrocks. Results have shown that Diolkos beachrock was formed in the upper part of the intertidal zone, consisting of detrital material originating from the local bedrock, while Sumuide beachrock formed in the low intertidal–upper subtidal zone, consisting of coral sand and foraminifera fragments. For the artificial beachrocks, three samples were created using the microbial-induced carbonate precipitation (MICP) method, one from Diolkos (Corinth, Greece) and two from Sumuide (Okinawa, Japan). Diolkos artificial beachrock was better consolidated in comparison to Sumuide. Our investigation has shown that bacterial density was the key factor for the creation of the artificial beachrocks, while the samples’ granulometry played a secondary role in the process. The laboratory artificial beachrocks show encouraging results for a new soft engineering method to encounter beach erosion while keeping an ecofriendly character by saving energy, material resources and gas emissions. Artificial beachrocks can share the same properties of a natural beachrock and can contribute positively to marine biodiversity as a natural rocky habitat.